Peran Brand Ambassador Arya Saloka dan Amanda Manopo dalam Membangun Brand Awareness - Randy Wijaya; Septia Winduwati (Kiwari, 2022)
This Research is trying to examine the role of brand ambassadors in increasing brand awareness. The researcher took the case study of Arya saloka and Amanda Manopo who became Shopee's Brand ambassadors. Researchers interviewed three informants and one expert of marketing communications. The purpose of this study was to determine the role of Brand ambassadors Arya Saloka and Amanda Manopo in building Brand Awareness. The researcher uses Kotler & Keller marketing communication theory and brand awareness theory with qualitative case study methods which data is taken from interviews, literature study and documentation study. The results that the authors get are that the brand ambassadors is one of factor in building brand awareness. Brand ambassador must have five attributes, namely suitability, transparency, attractiveness, power, and credibility. Brand ambassadors are important because they are a bridge between the community and the company. The three informants have reached the highest level in the brand awareness pyramid, namely the Top of Mind. The three informants know the elements of Shopee and Shopee users.Kajian ini meneliti peran brand ambassador dalam meningkatkan brand awareness. peneliti mengambil studi kasus Arya Saloka dan Amanda Manopo yang menjadi Brand ambassador Shopee. Peneliti mewawancarai tiga informan dan satu narasumber ahli di bidang komunikasi pemasaran. Tujuan penelitian ini ingin mengetahui peran Brand ambassador Arya Saloka dan Amanda Manopo dalam membangun Brand Awareness. Peneliti menggunakan teori komunikasi pemasaran Kotler&Keller dan teori brand awareness dengan metode kualitatif dengan metode studi kasus yang datanya diambil dari wawancara, studi kepustakaan dan studi dokumentasi. Hasil yang penulis dapatkan yaitu brand ambassador merupakan salah satu faktor dalam membangun brand awareness. Brand ambassador harus memiliki lima atribut yaitu kesesuaian, transparansi, daya Tarik, power, dan kredibilitas. Brand ambassador menjadi penting karena merupakan jembatan antara masyarakat dan perusahaan. Ketiga informan sudah mencapai tingkat tertinggi dalam piramida kesadaran merek yaitu puncak pemikiran (top of mind). Ketiga informan mengetahui elemen-elemen Shopee dan pengguna Shopee.